Experimental investigation on linear fresnel reflector prototype for solar heat production - Omar Achahour; Badreddine El Ghazzani; Rachid Safoui; Aicha Eddemani; Mohamed Abbassi; Abdeslam Elfanaoui; Ahmed Ihlal (Renewable Energy and Sustainable Development)
This paper deals with the conception, design, and construction of a prototype of a Linear Fresnel Reflector (LFR) coupled with a Multi-Effect Distillation system intended to sea-water desalination. Our system consists of 11 flat glass mirrors with a total reflecting surface of 1.5 m2, and a tubular receiver-absorber located inside an evacuated glass tube equipped with a secondary reflector. To deal with the discontinuity in heat production, a thermal storage system was built using locally abundant materials such as a bed-rock. An experimental study of the thermal and optical performances of the system has been assessed to quantify the overall efficiency of our prototype. The salient features of our study include a stagnation temperature as high as 263 °C, the overall heat transfer coefficient reached 22.91 W/m²K, and the estimated collector’s efficiency at an operating temperature of 125°C was 56%. TRNSYS simulation of an LFR system similar to the proposed prototype was conducted. It shows that the system's thermal output is highly influenced by both tank size and flow rate.   Received on, 26 March 2025 Accepted on, 10 May 2025 Published on, 15 May 2025